2004
DOI: 10.1002/art.20255
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD70 and overstimulation of IgG synthesis by lupus T cells and T cells treated with DNA methylation inhibitors

Abstract: Objective. Generalized DNA hypomethylation contributes to altered T cell function and gene expression in systemic lupus erythematosus (SLE). Some of the overexpressed genes participate in the disease process, but the full repertoire of genes affected is unknown. Methylation-sensitive T cell genes were identified by treating T cells with the DNA methyltransferase inhibitor 5-azacytidine and comparing gene expression with oligonucleotide arrays. CD70, a costimulatory ligand for B cell CD27, was one gene that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
182
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(188 citation statements)
references
References 36 publications
2
182
3
Order By: Relevance
“…DNMT inhibition increased CD70 expression in both cell types; however, the relative difference between CD4 ϩ CD28 Ϫ and CD4 ϩ CD28 ϩ T cells was maintained. In contrast, inhibition of the ERK pathway, which has recently been implicated in modifying methylation patterns of CD4 T cells in SLE patients (29), did not have any effects.…”
Section: Correlation Between Cd70 Promoter Demethylation and Cd70 Tramentioning
confidence: 58%
See 1 more Smart Citation
“…DNMT inhibition increased CD70 expression in both cell types; however, the relative difference between CD4 ϩ CD28 Ϫ and CD4 ϩ CD28 ϩ T cells was maintained. In contrast, inhibition of the ERK pathway, which has recently been implicated in modifying methylation patterns of CD4 T cells in SLE patients (29), did not have any effects.…”
Section: Correlation Between Cd70 Promoter Demethylation and Cd70 Tramentioning
confidence: 58%
“…CD70 overexpression is not only seen in RA patients; it has also been described in SLE (29,48). The mechanisms are different, but the functional consequences appear to be very similar.…”
Section: Discussionmentioning
confidence: 95%
“…30 Similar to the approach of our current study it was shown that normal T cells treated with 5-azaC upregulated LFA1, CD70 and perforin and that the CpG islands in the promoters of these genes were hypomethylated in T cells of systemic lupus erythematosus patients. [31][32][33] DNA methylation of promoter sequences can change the binding of transcription factors. …”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of these methylation-sensitive genes such as CD11a, and CD70 is also observed in patients with active lupus as well as in human T cells treated with DNA methylation inhibitors. 15,18 Microarray expression experiments performed on spleen RNA from mice with T-cell ERK signaling defect revealed differential expression of 60 genes. Interestingly, eight genes that are differentially expressed are interferon-regulated genes ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The hypomethylated cells also overstimulate autologous B-cell antibody production, due to demethylation and overexpression of the genes encoding CD70 (TNFSF7), and CD40L (CD40LG). 18,19 Importantly, procainamide and hydralazine, which cause anti-nuclear antibodies in a majority of people and a lupus-like disease in a subset, are DNA methylation inhibitors. 20 Procainamide is a competitive Dnmt1 inhibitor, 21,22 whereas hydralazine inhibits ERK pathway signaling, thereby decreasing Dnmt1 expression.…”
Section: Introductionmentioning
confidence: 99%